Coagulopathy as a complication of kidney biopsies in paediatric systemic lupus erythematosus patients with antiphospholipid syndrome. Issue 6 (10th June 2018) - Nagata, Hiroko; Sato, Mai; Ogura, Masao; Yoshikawa, Takahisa; Yamamoto, Kazuna; Matsumura, Sohshi; Kano, Yuji; Saida, Ken; Sako, Mayumi; Kamei, Koichi; Yoshioka, Takako; Ogata, Kentaro; et al.
ABSTRACT: Children with systemic lupus erythematosus (SLE) generally undergo a pretreatment kidney biopsy. However, some of these patients, especially those with antiphospholipid syndrome (APS), may experience serious coagulopathic complications. We report herein two cases of paediatric SLE with APS in which, despite normal blood test results, the disparate coagulopathic complications of haemorrhage and embolism developed following a kidney biopsy. Case 1 was, an 8‐year‐old male in whom, primary APS was initially diagnosed. Fourteen months later SLE was diagnosed. Based on a percutaneous kidney biopsy, International Society of Nephrology and the Renal Pathology Society (ISN/RPS) class III‐A lupus nephritis was histologically diagnosed. On post‐biopsy Day 9, a giant haematoma in the fascia of the left kidney developed and was accompanied by changes in the vital signs. Case 2, a 13‐year‐old male, initially received the diagnosis of SLE with APS and underwent two courses of pulse methylprednisolone therapy. His coagulation abnormalities improved, and a percutaneous needle kidney biopsy was performed, leading to the histological diagnosis of ISN/RPS class III‐A lupus nephritis. Furthermore, thrombotic microangiopathy was also detected in the renal histopathology. On post biopsy Day 6, the patient experienced right leg pain. A contrast CT and lower extremity ultrasonography detected a massive deep vein thrombosis and partial left pulmonary artery thrombosis. A kidney biopsy in children with SLE and APS can cause lethal coagulopathic complications, and the risks to such patients should be weighed carefully before the procedure is performed.